Removal of Cr(VI) with nano-FeS and CMC-FeS and transport properties in porous media. Issue 22 (1st October 2020) - Yang, Huiping; Hong, Mei; Chen, Shaoyin
ABSTRACT: We investigated the effect of CMC dosage on dispersibility and sedimentation of FeS, and the effects of initial Cr(VI) concentrations, reaction temperatures and initial pH values on the Cr(VI) removal by Nano-FeS and CMC-FeS through experiments. At the same time, the migration performance and deposition of Nano-FeS and CMC-FeS under different conditions were investigated. The results showed that: Nano-FeS aggregated to floc and precipitated. The 2.4% CMC-FeS had good dispersibility and anti-settling capacity. With the initial concentration of Cr(VI) increased from 10 to 50 mg L −1, the Cr(VI) removal efficiencies of Nano-FeS and CMC-FeS decreased. CMC prolonged reaction time between FeS and Cr(VI). When the reaction temperature increased from 10°C to 25°C, and the promotion of Cr(VI) reduction by CMC-FeS was higher than that of Nano-FeS. When the initial pH was 3–9, the Cr(VI) removal efficiencies of Nano-FeS and CMC-FeS were almost similar. But Cr(VI) removal by CMC-FeS was significantly higher than by Nano-FeS 23% at pH 12, which indicated that CMC-FeS still had high removal ability for Cr(VI) at high pH. From the breakthrough curves, the penetration ability ( Ci / C 0 ) of the two kinds of FeS nanoparticles in coarse, medium and fine sand was CMC-FeS > Nano-FeS. The maximum transport distance ( L max ) of CMC-FeS was 6.4 times longer than that of Nano-FeS in medium sand. The increase of FeS injection concentration resulted in more FeS deposition into the media, but the CMC modification could significantly reduce the deposition rate (k) and amount of deposition. GRAPHICAL ABSTRACT: UF0001